First Results of a Joint Bistatic Airborne SAR Experiment - Wendler, M.; Krieger, Gerhard; Horn, R.; Gabler, B.; Dubois-Fernandez, P.; Vaizan, B.; du Plessis, O. (International Geoscience and Remote Sensing Symposium 2003, Toulouse, 21.-25. Juli, 2003)
Future spaceborne SAR systems will operate in bi- and multistatic configurations to gain more information of the illuminated region. Such additional information might be the extraction of bistatic radar cross section or the simultaneous scene acquisition from different bistatic angles. Furthermore, a considerable cost reduction can be achieved by applying one radar illuminator and several passive receivers. For the definition of such SAR configurations, a bistatic airborne SAR experiment is being accomplished between the German Aerospace Center (DLR) and the French Office National dEtudes et de Recherches Aerospatiales (ONERA) with their airborne SAR systems E-SAR and RAMSES. One of the two radar systems serves both as transmitter and receiver while the other is receiving the back-scattered radar echoes. This paper describes the flight configurations for the data takes of the bistatic airborne SAR experiment resulting in different bistatic angles on the ground. Their influence on the processed radar images is shown. Platform motions are analysed, e.g. with respect to the resulting common antenna footprint. A precise GPS time signal is used for the nonrecurring one-time synchronisation of both radar systems directly before data acquisition. To follow this strategy, several modifications have been implemented into the systems which are described in detail. This strategy permits a sufficient phase and timing stability of both the transmitted and received radar signals during the time of a radar data take. Finally, a preliminary processing algorithm for bistatic SAR data is introduced and the status of the resulting radar data processing is presented.
DLR Import::2019-04-03